99 Investigating BMI-driven variations in cancer immunotherapy treatment effect: An individual patient data meta-analysis (2013–2023) - Pratik Reddy (Journal of Clinical and Translational Science)
Objectives/Goals: This study looks to investigate the relationship between body mass index (BMI) and the treatment effect of cancer immunotherapies. Specifically, we will assess whether there is a significant difference in survival curves associated with varying BMI levels and track trends in BMI reporting over the last decade. Methods/Study Population: An individual patient meta-analysis will be conducted by reanalyzing raw data of phase 3 cancer immunotherapy trials (2013–2023) accessed via the database Vivli. Prior to making a formal data request, an exploratory search will be first done through clinicaltrials.gov to assess viability. Studies that report baseline BMI and treatment efficacy will be included. BMI will be analyzed as a continuous variable, with survival curves compared across different BMI ranges using restricted mean survival time and log-rank tests. Trials will be stratified by drug class and adjusted for race, age, and gender to account for potential sources of confounding/bias. Results/Anticipated Results: Results are currently still a work in progress as I am in the process of getting the dataset from Vivli. I anticipate that treatment effects in cancer immunotherapies will vary significantly by BMI. Furthermore, I expect to see significant disparities in survival outcomes between patients assigned to a low and high BMI category. Lastly, trends in the reporting of BMI across immunotherapy trials are expected to be inconsistent which highlights the need for more standardization in clinical trial datasets. Discussion/Significance of Impact: This study should address critical knowledge gaps in how BMI level is associated with immunotherapy outcomes. These findings could potentially guide personalized treatment strategies and highlight the importance of standardizing the variables clinical trials chose to report.